Hubungan Gaya Kepemimpinan Kepala Puskesmas Dengan Kinerja Perawat di Puskesmas Sedati Kabupaten Sidoarjo - Nugraha, Mochammad Rama Surya; Herawati, Yennike Tri; Ridzkyanto, Ricko Pratama (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2025)
Background: Health is a basic human right and is guaranteed by the 1945 Constitution and Law Number 17 of 2023. Health centers as first-level health care facilities have the responsibility to improve the quality of service performance. One of the factors that influences nurse performance is the leadership style of the head of Primary Health Care. Aims: This study aims to analyze the relationship between the leadership style of the head of the Primary Health Care and the performance of nurses at the Sedati Primary Health Care, Sidoarjo Regency. Methods: The study used an observational analytical quantitative design with a cross-sectional approach conducted in March–April 2025. A sample of 35 nurses was taken using the total sampling technique. Data collection was carried out through interviews with questionnaires that had been tested for validity and reliability. Results: Data analysis used the Fisher Exact Test. The results showed that the majority of Health Center heads applied a democratic leadership style (57.1%) and most nurses had high performance (65.7%). The Fisher Exact Test showed a p value = 0.001 (<0.05), indicating a significant relationship between leadership style and nurse performance. Participative and communicative democratic leadership style has been proven to increase nurses' motivation and professionalism. Conclusion: This study concludes that effective leadership style has an important role in improving nurses' performance and the quality of health services at the primary level.